The Effect of Service Quality on Customer Loyalty of Generation Y - An Empirical Investigation on Superstores in Bangladesh - Alam, Mirza Mohammad Didarul (Universiti Utara Malaysia Press, 2018)
Today, retailers have been struggling to retain their existing customers in the face of severe competition in their business operations. By expanding the service quality, retailers will be able to stand out among the other businesses and create the opportunity to strengthen customer loyalty, particularly within the younger generation. The aim of this study is to propose and empirically investigate the mechanism of increasing customer loyalty of Generation Y (Gen Y) toward superstores by means of enhancing service quality practices. Based on a structured questionnaire, data was collected from 252 Gen Y consumers who have visited four leading superstores in Bangladesh. The data was analyzed through SEMPLS3.0 to test the validity of the measures and used to examine the hypothesized relationships by employing structural equation modeling. The findings show that the Retail Service Quality Scale (RSQS) is a reliable and valid instrument for assessing service quality in the retail sector of Bangladesh. The structural model indicates that the customer loyalty of Gen Y toward superstores is positively influenced by retail service quality dimensions such as policy, reliability, personal interaction, physical aspect, and problem solving, in the order of influencing strength. This paper provides the research implications and avenue for future research.